Language and identity in a dual immersion school - Potowski, Kim (Bilingual education and bilingualism ;, 2007)
Describes the experiences of a group of students in Chicago who are attending one of the first Spanish-English dual immersion schools in the United States. This book follows the group during two school years, documenting their Spanish use and proficiency, as well as how their two languages intersect with the ongoing production of their identities.